2008
DOI: 10.1039/b807492e
|View full text |Cite
|
Sign up to set email alerts
|

Solvent structures of mixed water/acetonitrile mixtures at chromatographic interfaces from computer simulations

Abstract: Atomistic simulations are used to characterize the molecular dynamics (MD) of alkyl chains with different functionalizations in different water/acetonitrile mixtures (80/20 and 50/50). Starting from fully equilibrated solvent systems (flat density profile for both components), microheterogeneous structuring of the solvent in the chromatographic system is found for both mixtures. Depending on the functionalization of the alkyl chain (nitrile, amide, nitro, phenyl), differences in the density profiles of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
73
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 32 publications
7
73
0
Order By: Relevance
“…Only few MD reports are available in the literature for RPLC-C 18 stationary phases in contact with various water/acetonitrile mixtures as the bulk mobile phase [32,24,26,35]. To the best of our knowledge, no investigations have yet been attempted to determine the density profiles of C 18 chains, water, and acetonitrile from actual excess adsorption data of acetonitrile recorded by the minor disturbance method [7][8][9].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Only few MD reports are available in the literature for RPLC-C 18 stationary phases in contact with various water/acetonitrile mixtures as the bulk mobile phase [32,24,26,35]. To the best of our knowledge, no investigations have yet been attempted to determine the density profiles of C 18 chains, water, and acetonitrile from actual excess adsorption data of acetonitrile recorded by the minor disturbance method [7][8][9].…”
Section: Introductionmentioning
confidence: 96%
“…Aqueous organic (methanol or acetonitrile) mixtures were used as the bulk mobile phases. Monte-Carlo molecular dynamics (MD) calculations have provided unprecedented data for the local density, solute distribution coefficients, and preferential orientations of analytes, solvent components, and C 18 materials [23][24][25][26][27][28][29][30][31][32][33][34][35]. These calculations also revealed that water is mostly excluded from the C 18 layer, the organic modifier penetrates deeper into it, polar analytes (n-propanol) concentrate in the interface region between the C 18 layer and the bulk phase, and that apolar analytes (n-butane) accumulate in two distinct regions deeper into the C 18 layer.…”
Section: Introductionmentioning
confidence: 99%
“…Acetonitrile (AN) and its mixtures with water are commonly used as reaction media in many different areas like organic synthesis [1,2], reverse phase liquid chromatography [3], electrochemistry [4], phase separation [5], hydrometallurgy [6,7], and atmospheric chemistry [8]. Their popularity arises from the unique characteristics of AN including its large value of dielectric constant and its ability to solvate many inorganic and organic materials [9].…”
Section: Introductionmentioning
confidence: 99%
“…In reversed-phase liquid chromatography, the bonded layers built of short alkyl chains grafted onto silica microspheres are used as the stationary phases and aqueous solutions of popular organic solvents (methanol, acetonitrile and tetrahydrofuran) as the mobile phases. The retention process on the homopolymeric-bonded phases was studied using SCFT [46], DFT [47], Monte Carlo simulations [48][49][50] and molecular dynamics [51]. In certain cases, however, to achieve a desired selectivity, one has to use the so-called polar-embedded phases which contain polar moieties within the alkyl chains [52].…”
Section: Introductionmentioning
confidence: 99%